MOLECULAR DIAGNOSIS AND COMPARISON STUDY TO THE RED PALM WEEVIL RHYNCOPHOROUS FERRUGINEUS (OLIVIER, 1790) IN BASRAH PROVINCE - IRAQ - & Aletby, Al-Saad (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
The Red Palm Weevil (RPW) Rhynchophorus ferrugineus (Olivier) is well-known as serious insect pest of date palm and other palm species. The pest was firstly recorded in Iraq in 2015. This study was confirmed the identification of this pest using molecular diagnostic (PCR and sequence analysis) and investigate the genetic relationship by comparison of the sequences with other recorded copies worldwide. The results confirmed the identity of the R. ferrugineus (Olivier) molecularly. Ten copies of mitochondrial COI gene of Iraqi samples (MF092880.1- MF092889.1) were firstly registered in National Center of Biotechnology Information (NCBI). The sequences comparison of Iraqi sample genes with worldwide genes showed high similarity with Chinese and Mediterranean COI copies especially the Tunisian one, which may assumes that they were descended from the same origin. The study concluded that the invention of this insect to Iraq could be occurred directly from farms in border area between Iraq and Kuwait or by infested offshoot that imported from other countries.